Bayad utang - Puangco, Renato (Animo Repository, 2005)
The neighborhood, a harsh environment where gangs constantly feud. The locale, people who struggle to merely survive day to day. The protagonist, a lost youth trying to make sense of and find his way in the world. The video starts with a fight between two rival gangs. Amidst the chaos Ermes (Mes) Santiago notices an innocent by standard who is accidentally killed. He runs to the kid in an attempt to help. Unaware of what just happened, Caloy Braganza looks around and sees Mes standing over the body of Raffy, his younger brother. Tomas Ramirez is a confused teen who us hard on his luck and has a lot of problem with his family. He constantly butts head with his mom who always pushes him to help out with their situation. As a solution to his problems he decides to join a gang in hopes to make things better. One day Tomas sees Mes, a cousin he hasn't seen in a long time. As they catch up, Tomas confides his plans of joining a gang but is told to think twice before doing so. Caloy's interest is aroused when he finds out that a neophyte of the gang he now leads is related to the man he believes responsible for his brother's death. With this information, he intends to use Tomas to get his revenge. After finding out that Tomas went on with his plan, Mes is bothered by Tomas's attitude after being accepted into the gang. In a final attempt to get through to Tomas, Mes crosses paths with Caloy in an unfortunate confrontation that makes Tomas opens his eyes to the reality of what he got himself into. He knows the possibility that one day he will have to pay his dues, just as Caloy and Mes faces the consequences of their own actions.